2015
DOI: 10.1371/journal.pone.0129506
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Data Sharing and Reuse: Attitudes and Practices of Clinical and Scientific Research Staff

Abstract: BackgroundSignificant efforts are underway within the biomedical research community to encourage sharing and reuse of research data in order to enhance research reproducibility and enable scientific discovery. While some technological challenges do exist, many of the barriers to sharing and reuse are social in nature, arising from researchers’ concerns about and attitudes toward sharing their data. In addition, clinical and basic science researchers face their own unique sets of challenges to sharing data with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
114
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(122 citation statements)
references
References 35 publications
8
114
0
Order By: Relevance
“…The vast amount of data already available in these repositories demonstrates that many researchers are open to sharing their data, though research has demonstrated that researchers' willingness to share their data may vary widely depending on a variety of factors, including their field of research, years of experience in the field, and type of funding [13,31,34]. However, regardless of whether a researcher feels open to sharing their data or not, chances are good that most researchers will soon be required to do so.…”
Section: Introductionmentioning
confidence: 99%
“…The vast amount of data already available in these repositories demonstrates that many researchers are open to sharing their data, though research has demonstrated that researchers' willingness to share their data may vary widely depending on a variety of factors, including their field of research, years of experience in the field, and type of funding [13,31,34]. However, regardless of whether a researcher feels open to sharing their data or not, chances are good that most researchers will soon be required to do so.…”
Section: Introductionmentioning
confidence: 99%
“…There is an identified need for a framework that builds familiarity, trust, mutual purpose and dependency across a data sharing community of practice that allows risks to be understood and mitigated [19]. Whilst technical challenges are not trivial and solutions are essential, a key message in the literature is that cultural factors are likely to be harder to solve [18,21].…”
Section: Findings From the Literature On Data Sharingmentioning
confidence: 99%
“…Table 2 Reasons for Not Sharing Data from NIH Study (Federer et al, 2015) Digital research data storage amounts and locations from Emory survey (Akers & Doty, 2013).…”
Section: • Roy Brown Work On Nurses Magnetmentioning
confidence: 99%